Response of bitter gourd (Momordica charantia) seed to seed priming treatments under sub-optimal environments - SINGH, RAJINDER; BASSI, GEETA (The Indian Journal of Agricultural Sciences, 2016)
To overcome the problem of delayed, non-uniform and poor seed emergence in bitter gourd (Momordica charantia L.), an experiment was laid out in a randomized complete block design (RCBD) with a factorial arrangement during winter and spring season of 2012, 2013 and 2014 at the Research Farm of the Department of Vegetable Science, Punjab Agricultural University, Ludhiana. The treatments consisted of two environments (sowing during third week of January and February) and 18 priming treatments (soaking for 24h in GA3 100 and 500 ppm, potassium dihydrogen orthophosphate (KH2PO4) 10-1M and 10-3M, sodium dihydrogen orthophosphate (NaH2PO4) 10-1M and 10-3M, 0.1% potassium nitrate (KNO3);only hydration followed by burying in farm yard manure for 48hr). The seeds from all these treatments were kept in moist gunny bags for two different durations, i.e. 24 and 48 hr, respectively, at room temperature. Untreated seeds served as control. Following this, the treated seeds were air dried at room temperature and then sown in polythene bags. Emergence per cent (79.22 and 79.67) and speed of emergence (4.45 and 4.75) in each environment was better when seeds were treated with 10-1M KH2PO4 and incubated in gunny bags for 48 hr. However, February sown seeds emerged earlier and faster than January sown seeds. Seedling length and seedling fresh weight were highest when seed were treated with 500 ppm GA3 but statistically at par with 10-1M KH2PO4. Other seed quality parameters like seedling dry weight, vigour index-I and II were also superior with 10-1M KH2PO4.Therefore it was inferred that to improve the germination of bitter gourd seeds under optimal and sub-optimal temperature, it should be soaked for 24 hr in 10-1M KH2PO4 followed by keeping in moist gunny bags for 48 hr.